Universidad Complutense, CBVM Biogeoclimatic Madrid Framework - Sanchez-Mata, Daniel (2009)
Arctic Council´s Conservation of Arctic Flora and Fauna Working Group´s (CAFF) Circumpolar Flora Group Proceedings.